Proyecto de plan de marketing y comercialización del producto dulce de zapallo, elaborado por la microempresa alimentos peninsulares (alipen) - Manzini Chaguay, Corina (2010)
The Ecuadorian market, has many products that are purchased to be part of the breakfasts, special meetings or to consume at the time that we feel like such as: sweets, treats, or jams that are made from fruit among which are traditional strawberry, pineapple, blackberry. For this reason, we want to make available to consumers a new product made from squash called "Sweet Pumpkin Dupyz" featuring a different flavor and pleasing to the palate. Because the small business Food Peninsular (ALIPEN) has not considered a great opportunity to attract consumers to expand their products based on organic pumpkin into new markets is considered to make a marketing and marketing plan to publicize the small business and its most important product " Sweet Pumpkin Dupyz " in the city of Guayaquil